Performance analysis of more electric aircraft starter/generator by different electric loads - Kaya, Ufuk; Oksuztepe, Eyyup (Inderscience Enterprises Ltd, 2023)
The more electric aircraft is a trending topic in aviation studies. This topic comprises a wide range of applications that are directly related to electrical machines and power electronics. The starter/generator is one of these remarkable applications, and it is used for main engine cranking and required electrical power generation. In comparison with conventional starter and generator systems, the starter/generator is more robust, reliable, and cheap. Also, it requires almost no maintenance. Considering the increased demand for electrical power in commercial and military aircraft, the interest in starter/generators is increased in terms of scientific studies and industrial applications. In this study, a 20 kW starter/generator based on a three-phase surface-mounted permanent magnet synchronous machine is proposed and model reliability is tested with different types of and power-rated electrical loads. The proposed model is simulated at MATLAB/Simulink with Simscape blocks. The results show that the SG has sufficient performance for starter, and generator operation.
Keywords: more electric aircraft; MEA; starter; generator; aircraft; permanent magnet synchronous machine; PMSM; electrical power generation